Mr. Popper's penguins : - Atwater, Richard (Little, Brown and Co., 2009)
The unexpected delivery of a large crate containing an Antarctic penguin changes the life and fortunes of Mr. Popper, a house painter obsessed by dreams of the Polar regions.